Horizontal vs vertical investment returns analysis using fundamental indicators / Nurfatehah Azni - Azni, Nurfatehah (2017)
This paper attempts to investigate the relationship between firm specific variables and stock returns. This research also sought to investigate the effect of economic variables on stock returns in Malaysia. Four variables are used as control variables in explaining the stock returns, namely firm size, book-to-market equity, gross domestic product (GDP) and interest rate. This study which covers the period of 2011 until 2015 comprised 30 selected companies listed in Malaysian stock market. The general findings reveal that book-to-market equity has a significant relationship with stock returns and GDP and inflation rate have a significant effect towards stock returns in construction, consumer production and manufacturing industries.